Anti-Saccaromyces Cerevisiae antibodies (ASCA) are elevated in autoimmune thyroid disease ASCA in autoimmune thyroid disease - YAVUZ, DİLEK; ÜSTAY, ÖZLEM; DİRESKENELİ, RAFİ HANER (SPRINGER, 2010)
Environmental factors have been implicated in the development of autoimmune thyroid disease (AITD). Anti-Saccaromyces Cerevisiae Antibodies (ASCA) were shown to be elevated in several autoimmune diseases. The aim of the study was to determine ASCA levels and their relationship with thyroid autoantibodies in patients with AITD. One-hundred and twelve patients with AITD (age 41.1 +/- 12.8 years; F/M: 96/16) and 103 healthy controls (38.5 +/- 10.3 years; F/M: 82/21) were included. Twenty-four patients had Graves disease (GD), and 88 had Hashimoto's thyroiditis (HT). ASCA IgA and IgG, TSH, free T4, anti-thyroglobulin, and anti-thyroid peroxidase antibody concentrations were determined. ASCA IgA positivity in patients with GD (16.6%) was similar to patients with HT (13.6%) and was higher than controls (5.8%). No significant difference was present between the frequencies of IgG positivity among GD (12.5%), HT (7.9%), and control groups (5.8%). The mean levels of ASCA IgA and IgG were comparable within the groups. No correlation of ASCA and anti-thyroglobulin and antithyroid peroxidase levels was observed. Increased IgA ASCA positivity is observed in patients with GD, suggesting a role of environmental stimuli in its pathogenesis. The role of ASCA in the etiology of AITD needs to be further examined.
Keywords: ASCA; Autoimmune thyroid disease; Graves disease; Hashimoto's thyroiditis; INFLAMMATORY-BOWEL-DISEASE; CROHNS-DISEASE; CELIAC-DISEASE; ULCERATIVE-COLITIS; GRAVES-DISEASE; SACCHAROMYCES; AUTOANTIBODIES; PATHOGENESIS; DISORDERS